PENGETAHUAN ORANG TUA TENTANG DAMPAK PENGGUNAAN GADGET PADA ANAK PRASEKOLAH DI RA PERSIS 16 KECAMATAN CIAWI KABUPATEN TASIKMALAYA - farwa amaani zahida; aap apipudin; nur hidayat (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2020)
Child recognition of gadgets usually starts from the wrong way of transfer from parents or family by showing the game or video on the gadget. The introduction of gadgets too early in children can have both positive and negative effects. This is influenced by several factors such as the frequency, duration, and supervision of parents in the hope that children are not fussy or stop crying. Knowledge, is a very important domain for the formation of actions so that the existence of good knowledge about gadgets will influence the behavior of parents in providing gadgets to preschoolers Descriptive research method with quantitative approach. The population in this study were all parents of pre-school children in RA Persis 16, Ciawi District,Tasikmalaya Regency, in 2018 as many as 64 people. Sampling in this study using total sampling technique that is the entire population used as research samples.The results showed that knowledge about the impact of using gadgets on preschool children in RA PERSIS 16, Ciawi Subdistrict, Tasikmalaya District, were mostly lacking knowledge as many as 34 people (53.1%). Suggestions are expected that parents be more active in asking questions, seeking information and attending counseling about the impact of using gadgets on preschoolers.